A chemiluminescent probe for cellular peroxynitrite using a self-immolative oxidative decarbonylation reaction. Issue 9 (7th February 2018) - Cao, Jian; An, Weiwei; Reeves, Audrey G.; Lippert, Alexander R.
Abstract : Peroxynitrite is a damaging agent of oxidative stress that has been difficult to monitor in living cells. Here, an isatin-based chemiluminescent probe for peroxynitrite is reported. Abstract : Peroxynitrite (ONOO − ) is a highly reactive oxygen species which has been recognized as an endogenous mediator of physiological activities like the immune response as well as a damaging agent of oxidative stress under pathological conditions. While its biological importance is becoming clearer, many of the details of its production and mechanism of action remain elusive due to the lack of available selective and sensitive detection methods. Herein, we report the development, characterization, and biological applications of a reaction-based chemiluminescent probe for ONOO − detection, termed asPNCL .PNCL reacts with ONOO − via an isatin moiety through an oxidative decarbonylation reaction to initiate light emission that can be observed instantly with high selectivity against other reactive sulphur, oxygen, and nitrogen species. Detailed studies were performed to study the reaction between isatin and ONOO −, which confirm selectivity for ONOO − over NO2 ˙.PNCL has been applied for ONOO − detection in aqueous solution and live cells. Moreover, PNCL can be employed to detect cellular ONOO − generated in macrophages stimulated to mount an immune response with lipopolysaccharide (LPS). The sensitivity granted by chemiluminescent detection together with the specificity of the oxidative decarbonylation reaction provides a useful tool to explore ONOO − chemistry and biology.